SISTEM PAKAR DIAGNOSA PENYAKIT THT (TELINGA, HIDUNG, TENGGOROKAN) MENGGUNAKAN METODE CERTAINTY FACTOR (STUDI KASUS : RSUD H. ABDUL MANAP JAMBI): CERTAINTY FACTOR, EXPERT SYSTEM, ENT DISEASES - Simorangkir, Lucy (FORTECH (Journal of Information Technology), 2018)
ENT disease (ear, nose, and throat) is a health problem that many people suffer anytime and anywhere. However, many people still less knowledgeable about the diseases. It causes mild diseases that could be treated early, develop into serious illness due to lack of information about the symptoms.  RSUD H.Abdul Manap Jambi is one of the government hospitals. They  provides ENT clinic facilities for examinee ear, nose and throat diseases. Patient that want to consult or conduct an ENT examination with an ENT specialist should first register before they can see a doctor for consultation or examination. The expert system of ENT disease diagnosis is built with the aim to adopt expert knowledge (in this case, ENT specialists) so patients can do a preliminary examination of disorders related to ear problems, nose, and throat independently before seeing the doctor. This application could help them have early description obout the ENT diseases they suffer from.  Examination of the ssymptoms  processes by certainty factor where every symptom has certainty value that determined by the expert. Inputs in this system are patient data, symptom data, disease data, knowledge data and polling data. The outputs of this system are patient data reports, symptom data, disease data, knowledge data, diagnostic results, and poll results. The results show that this expert system can help the doctor's job become easier so it can give the diagnosis of ENT disease.